A educação dos filhos na palma das mãos: análise dos discursos sobre a Lei da Palmada no Facebook - Multari, Paula Perim Negrão (2020)
This research analyzes the antagonistic discourses in the comments of readers on Facebook about the Menino Bernardo Law, known as the Law of Spanking, and about physical punishment as a way of educating children. The corpus was build on posts and readers' comments on the posts on this topic, published on the Facebook pages of the newspapers O Globo and Folha de S.Paulo between 2010, when the discussion about the law took shape, untill October 2019, five years and three months after its approval. These comments are mapped and brought to the discourse analysis based on the theories of Patrick Charaudeau and exposed to the semiotics of Denis Bertrand. The analysis of how these discourses are articulated in social networks is carried out based on Manuel Castells' theories. As a theoretical and contextual basis, we provide an overview of physical punishment in Brazil and the impact on children's development with the support of Phillipe Ariès and Elisabeth Badinter